Effects of shifting from in-person to distributed work on routine, creative, and social collaboration - Rotter Šešok, Sara (Dynamic relationships management journal, 2024)
This study explores how the transition to distributed work environments has impacted collaboration processes, team dynamics and overall productivity in Microsoft, Google, Facebook, and Salesforce, all global technology companies included in the Fortune 500 top US companies list. It also examines the role of corporate culture, leadership, social and psychological factor, technological infrastructure, and individual customization in shaping these outcomes. In addition, it discusses strategies for optimizing collaboration in distributed forms of work that balance technological advances with the need for interpersonal interaction. This study contributes to the growing discourse on distributed work and provides valuable insights for organizations navigating this evolving work landscape. The research uses a qualitative approach that enables a deep investigation of the impact that distributed work has had on different types of employee collaboration (i.e., routine, creative and social) and the key factors contributing to a successful transition to distributed work. The findings reveal a differentiated landscape in which distributed work offers flexibility and potential individual productivity gains, but also presents challenges in maintaining effective team cohesion and spontaneous communication.
Keywords: kadri; knowledge transfer; personnel; prenos znanja; teamwork; timsko delo